2018
DOI: 10.1016/j.jallcom.2018.02.260
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performance of nanosized MnO2 synthesized by redox route using biological reducing agents

Abstract: For more than a century, manganese dioxides (MDOs) have been used as electrochemically active materials in energy storage and conversion applications. To reduce the cost and hazardous impact of synthesis, a redox method was used to prepare MnO2 using extracts of green (GT-MnO2) and black (BT-MnO2) tea as biological reducing agents. Polyphenols present in the extracts of tea not only reduce Mn 7+ ions but also act as "capping agents" to stabilize and prevent the produced MnO2 nanoparticles from degradation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 73 publications
6
36
0
Order By: Relevance
“…The combination of XRD data and HRTEM image reveals that NNs are composed of a few aggregated crystallites. This result is comparable with those obtained from α-KyMnO2 nanoneedles prepared by the mild synthetic method using the extract of tea as reducing agent, in which XRD patterns are dominated by the (211) Bragg line and the crystallite size is found to be ~4 nm [27]. Figure 3b shows the N2 adsorption desorption isotherm and Barrett-Joyner-Halenda (BJH) poresize distribution for as-prepared α-KyMnO2.…”
Section: Morphology Structure and Compositionsupporting
confidence: 79%
See 4 more Smart Citations
“…The combination of XRD data and HRTEM image reveals that NNs are composed of a few aggregated crystallites. This result is comparable with those obtained from α-KyMnO2 nanoneedles prepared by the mild synthetic method using the extract of tea as reducing agent, in which XRD patterns are dominated by the (211) Bragg line and the crystallite size is found to be ~4 nm [27]. Figure 3b shows the N2 adsorption desorption isotherm and Barrett-Joyner-Halenda (BJH) poresize distribution for as-prepared α-KyMnO2.…”
Section: Morphology Structure and Compositionsupporting
confidence: 79%
“…Using different DTG behaviors of the literature, it was found that there is an almost linear relationship between the transition temperature and the content of K + ions in α-K x Mn 8 O 16 . According to Figure 2 shown in [27], we can estimate a concentration of potassium (i.e., x = 0.035), which is close to the value obtained from ICP measurement. Thus, the amount of electrochemically inactive K + ions (1.45 wt.%) is confirmed to be much smaller than that of Mn (52.82 wt.%), and does not obviously affect the specific capacity of the electrode.…”
Section: Morphology Structure and Compositionsupporting
confidence: 78%
See 3 more Smart Citations